2020
DOI: 10.1371/journal.pntd.0008339
|View full text |Cite
|
Sign up to set email alerts
|

Spiro-containing derivatives show antiparasitic activity against Trypanosoma brucei through inhibition of the trypanothione reductase enzyme

Abstract: Trypanothione reductase (TR) is a key enzyme that catalyzes the reduction of trypanothione, an antioxidant dithiol that protects Trypanosomatid parasites from oxidative stress induced by mammalian host defense systems. TR is considered an attractive target for the development of novel anti-parasitic agents as it is essential for parasite survival but has no close homologue in humans. We report here the identification of spiro-containing derivatives as inhibitors of TR from Trypanosoma brucei (TbTR), the parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…TR from L. infantum was produced as previously reported. TR from T. brucei (TbTR) was produced as previously reported ( Turcano et al, 2020 ), with minor modifications. Briefly, the gene corresponding to TbTR (Uniprot ID: Q389T8) was cloned in the pET15b vector using the restriction site NdeI and XhoI to add an N-terminal His-tag.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TR from L. infantum was produced as previously reported. TR from T. brucei (TbTR) was produced as previously reported ( Turcano et al, 2020 ), with minor modifications. Briefly, the gene corresponding to TbTR (Uniprot ID: Q389T8) was cloned in the pET15b vector using the restriction site NdeI and XhoI to add an N-terminal His-tag.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Considerable effort has been put together to identify new hits targeting TR, rationalize the interaction through structural characterization, and improve known scaffolds through SAR studies or structure-based design ( Bernardes et al, 2013 ; Field et al, 2017 ; Battista et al, 2020 ), but despite some remarkable results ( Patterson et al, 2011 ; De Gasparo et al, 2018 ; Turcano et al, 2018 ; De Gasparo et al, 2019 ; Turcano et al, 2020 ), none of the leads proposed has been yet promoted to preclinical trials, due to sub-optimal activity or toxicity issue. Most characterized inhibitors were found to target the TSH cavity, mainly the so-called mepacrine binding site (MBS) located at the entrance of the TSH cavity.…”
Section: Introductionmentioning
confidence: 99%
“…TR from L. infantum and from T. brucei were expressed and purified as previously reported. 17,29,33 Briefly, the genes, coding for the enzymes (aa 1−492) and codon optimized for the expression in E. coli, were obtained from GenScript. The coding sequences were then cloned in the pET15b vector to have an N-terminal fused 6xHisTag for purification purposes.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Recent years have witnessed a significant research effort toward the identification of effective modulators of the enzymes involved in T­(SH) 2 metabolism, which are both necessary for parasite survival and absent in the human host. Since several years, we have focused on the design, synthesis, and evaluation of novel molecular scaffolds as anti- Leishmania agents that can also interfere with the trypanothione metabolism. Among the drug targets explored in this field, it has been demonstrated that pentavalent antimonials affect the TR activity, which is essential for survival of Leishmania inside the macrophages. , Moreover, due to its structural and sequence similarity to TR from other trypanosomatids such as T. brucei and T.…”
mentioning
confidence: 99%
“…Also, to achieve an adequate trypanocidal effect, TyrR activity must be inhibited by up to 90% due to the enzyme's elevated efficacy in terms of turnover [207,211]. A spiro derivative molecule has been determined to differentially inhibit trypanothione reductase, having no modulatory effect on human glutathione reductase [212]. Spiro molecules serve as a scaffold for BBB-penetrant molecules [212].…”
Section: Oxidative Stress/polyamine Synthesis-trypanothione Systemmentioning
confidence: 99%